Malignant glioma: The involvement of loss of allelic heterozygosity and PTEN mutations in a group of Malay patients - Zainuddin, Norafiza; Jaafar, Hasnan; Isa, Mohd. Nizam; Abdullah, Jafri Malin (Faculty of Tropical Medicine, Mahidol University, 2005)
Frequent loss of heterozygosity (LOH) and mutations of the tumor suppressor gene PTEN (phosphatase and tensin homologue deleted from chromosome 10) have been found in sporadic gliomas. The most documented regions of allelic losses include 9p21, 10q23-25 and 17p13 whereas PTEN aberrations are preferentially found in glioblastoma multiformes. This research aimed to detect the incidence of allelic losses on chromosomes 10q, 9p, 17p and 13q and mutations on exons 5, 6 and 8 of PTEN in malignant gliomas. Malignant glioma specimens obtained were classified histopathologically according to the WHO criteria. Each tumor was then subjected to polymerase chain reaction (PCR)-LOH analysis using microsatellite markers and single-stranded conformational polymorphism (SSCP) analysis. Twelve of 23 (52%) malignant glioma cases showed allelic losses whereas 7 of 23 (30%) samples showed aberrant band patterns and mutations of PTEN. Four of these cases showed LOH in 10q23 and mutations of PTEN. The data on LOH indicated the involvement of different genes in the genesis of glioma whereas mutations of PTEN indicated the role of PTEN tumor suppressor gene in the progression of glioma in Malay population.